2000
DOI: 10.1071/ea98013
|View full text |Cite
|
Sign up to set email alerts
|

Soil factors affecting the sustainability and productivity of perennial and annual pastures in the high rainfall zone of south-eastern Australia

Abstract: A field study was carried out in the high rainfall zone (HRZ, >600 mm p.a.) of southern Australia from March 1994 to August 1997 to test the hypothesis that sown perennial grasses and liming could make the existing pastures more sustainable through better use of water and nitrogen. The site, on an acid duplex soil at Book Book near Wagga Wagga in southern New South Wales, was typical of much of the HRZ grazing country in southern New South Wales and north-east Victoria. The experiment consisted of 4 replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 36 publications
0
26
0
1
Order By: Relevance
“…These authors determined higher rates of deep drainage under annual grasses than under perennials, given like conditions. White et al (2000), for instance, reported higher deep drainage rates of 38-40 mm under annual pastures. Similar observations were also reported by Walker et al (1981); White et al (2000) and Virgona and Southwell (2006) under rangeland conditions.…”
Section: Soil-water and Savanna Plantsmentioning
confidence: 97%
See 1 more Smart Citation
“…These authors determined higher rates of deep drainage under annual grasses than under perennials, given like conditions. White et al (2000), for instance, reported higher deep drainage rates of 38-40 mm under annual pastures. Similar observations were also reported by Walker et al (1981); White et al (2000) and Virgona and Southwell (2006) under rangeland conditions.…”
Section: Soil-water and Savanna Plantsmentioning
confidence: 97%
“…Differences with respect to water use are particularly apparent from studies comparing annual and perennial planted pastures as reported by Ridley et al (1997); White et al (2000); Heng et al (2001) and Bird et al (2004), and covering a range of species, soils and climatic conditions. These authors determined higher rates of deep drainage under annual grasses than under perennials, given like conditions.…”
Section: Soil-water and Savanna Plantsmentioning
confidence: 99%
“…This makes perennial crops highly competitive, both under erratic rainfall patterns and moisture deficits. In addition, the greater root mass of perennials reduces soil erosion risks (Gomiero et al 2011, Pimentel et al 2012) and soil salinization (White et al 2000, Ward et al 2006, maintains higher soil carbon sequestration potential, and ensures more efficient nutrient utilization through improved synchrony and nutrient conservation than annual crops (Randall and Mulla 2001, Crews 2005, Cox et al 2006.…”
Section: Ecological Potentials and Challenges Of Perennial Grain Cropsmentioning
confidence: 99%
“…) and soil salinization (White et al. , Ward et al. ), maintains higher soil carbon sequestration potential, and ensures more efficient nutrient utilization through improved synchrony and nutrient conservation than annual crops (Randall and Mulla , Crews , Cox et al.…”
Section: Introductionmentioning
confidence: 99%
“…Lower perennial grass content may lead to decreased livestock performance through increased variability in production over time and poorer quality summer forage . The loss of perennial grasses is also linked with environmental impacts such as soil erosion, soil acidification and the development of dryland salinity through poor control of the water table ; see also Ridley et al 1999;Scott et al 2000;White et al 2000).…”
mentioning
confidence: 99%